Consumer preferences for organic and fair trade chocolate: Implications for sustainable agriculture in the developing world - David S. Connor; Edward T. Mabaya (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2006)
This paper examines results of a consumer survey measuring consumer awareness and attitudes concerning two labels, certified organic and certified Fair Trade. These labels provide information about the social, economic and environmental sustainability of the production and marketing practices of goods imported from the developing world. Conjoint analysis is used to measure how consumers value organic and fair trade compared to other attributes like price. Results indicate favorable attitudes and value placed on these the sustainable attributes, and imply a role for these labels to provide incentives for the adoption of more sustainable practices.
Keywords: 330; conjoint analysis; fair trade; organic